Tourism and Modernity in 19th century Portugal: Ramalho Ortigão’s national waterscapes travel books - Gómez Vázquez, José Luis (LIT&TOUR – International Journal of Literature and Tourism Research (IJLTR), 2023)
Among his travel writing works, the Nineteenth Century Portuguese writer Ramalho Ortigão was dedicated to the knowledge of his national territory. He published Banhos de caldas e águas minerais (Thermal baths and mineral waters) and As praias de Portugal (Portugal beaches), two books that remarked on the qualities of Portugal as a privileged waterscape country with a great potential for the development of tourism. As an heir of literary Romanticism but also as a positivist, the author created a very particular discourse within those books: tensions between nationalism or cosmopolitanism, artistic and scientific aims, and even literary or pragmatic discourse reside in both texts. Explaining such tensions brought about philosophical concepts to the scene: the German philosopher Peter Sloterdijk used the term Verwöhnung (pampering) to describe new social needs oriented to relief and comfort, like the idea of vacation. In Ramalho’s time, Portuguese waterscapes began to satisfy those needs, and a type of national proto-Tourism took shape. Besides, pampering was not only related to relief but also to health. Medical sciences contributed to a social transformation and recreational places became a necessity rather than a luxury. Massive and rapid transportation, mostly trains, supplied citizens with quick and safe access to beaches and thermal waters. The methodology consists in discussing Ramalho’s observations about his travels across the waterscapes of Portugal considering Sloterdijk’s ideas on pampering in Modernity, some of which can be applied to the Portuguese reality of the nineteenth century. By reading Ramalho’s Banhos de caldas e águas minerais and As praias de Portugal under the philosophical framework of Peter Sloterdijk, it is possible to understand the deep entailment between the development of tourism as a response to modern life needs and the transformations of the literary discourse, that gained levity and gradually prioritized informative function instead of the aesthetic one.